A biosynthesis view on nutrient stress in coastal phytoplankton. (5th December 2016) - Grosse, Julia; van Breugel, Peter; Brussaard, Corina P. D.; Boschker, Henricus T. S.
Abstract: Anthropogenic activities resulted in major shifts in nutrient inputs to coastal seas, which may have altered the biomolecule composition of phytoplankton because of different C : N : P requirements for biosynthesis. In order to understand the effects of N‐ and P‐limitation on the allocation of photosynthetically fixed C, we directly measured seasonal and spatial dynamics of amino acid, fatty acid and carbohydrate concentrations and biosynthesis rates in the phytoplankton of the North Sea using a novel 13 C‐tracer approach. Nutrient limitation and season had large effects on composition and biosynthesis rates of all biochemical classes, for instance the contribution of protein derived amino acids varied up to fourfold in concentration and up to eightfold in biosynthesis rates. Nutrient specific effects and the prevailing nutrient limitations were identified by short‐term (24–72 h) nutrient addition experiments. Addition of the growth‐limiting nutrient increased amino acid synthesis while storage compound synthesis decreased concurrently. The strongest effect was detected in N‐limited flagellates, where amino acid synthesis increased up to fivefold within 24 h upon relief of nutrient limitation. P‐limitation was only detected in diatom‐dominated near‐coast stations, and amino acid synthesis responded much slower, likely because of the necessary preceding synthesis of ribosomes. This metabolic elasticity of phytoplankton in response to nutrient availability will have major consequences for their nutritional value within the food web and subsequently the carrying capacity of coastal ecosystems.